2016
DOI: 10.3389/fnins.2016.00510
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Progressive Neurodegeneration in a Transgenic Mouse Model of Prion Disease

Abstract: Neurodegenerative diseases present pathologically with progressive structural destruction of neurons and accumulation of mis-folded proteins specific for each condition leading to brain atrophy and functional disability. Many animal models exert deposition of pathogenic proteins without an accompanying neurodegeneration pattern. The lack of a comprehensive model hinders efforts to develop treatment. We performed longitudinal quantification of cellular, neuronal and synaptic density, as well as of neurogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 58 publications
(66 reference statements)
1
4
0
Order By: Relevance
“…8 B). This was consistent with a number of studies that have detected increased neurogenesis in the hippocampus [ 20 , 22 ] which may protect against prion disease [ 34 ]. Relatively few transcripts of neural progenitors were differentially expressed (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…8 B). This was consistent with a number of studies that have detected increased neurogenesis in the hippocampus [ 20 , 22 ] which may protect against prion disease [ 34 ]. Relatively few transcripts of neural progenitors were differentially expressed (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, we observed increased relative frequency of proliferating cell populations in the prion-infected brain, including neural progenitor cells, oligodendrocyte progenitor cells and proliferating microglial subtypes. While the relative frequencies presented here do not equate to true measurements of absolute cell count, previous studies have implicated proliferation of microglia [ 74 ] and neural progenitor cells [ 20 , 22 ] during prion disease. We speculate that a common means exists to promote cell proliferation during prion disease—possibly in an unsuccessful attempt to restore brain cells that are lost during disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, different studies reported reduced [40][41][42][43], normal [25], or enhanced [19,44] long-term potentiation (LTP) in Prnp 0/0 mice compared to wild-type mice. Following these descriptions, the consequences of Prnp absence in memory, learning, and behavior lead to variable results in studies using mice carrying FGs [24,[45][46][47][48] or not [42,49].…”
Section: Introductionmentioning
confidence: 99%
“…For example, different studies reported reduced (Collinge et al, 1994;Criado et al, 2005;Curtis et al, 2003;Manson et al, 1995), normal (Lledo et al, 1996), or enhanced (Maglio et al, 2006;Rangel et al, 2009) long-term potentiation (LTP) in Prnp 0/0 mice compared to wild-type mice. Following these descriptions, the consequences of Prnp absence in memory, learning, and behavior include variable results in studies using mice carrying FGs (i.e., (Bueler et al, 1992;Coitinho et al, 2003;Fainstein et al, 2016;Lipp et al, 1998;Schmitz et al, 2014b)) or not (i.e., (Criado et al, 2005;Manson et al, 1994)).…”
Section: Introductionmentioning
confidence: 99%
“…For example, different studies reported reduced [40][41][42][43], normal [25], or enhanced [19,44] long-term potentiation (LTP) in Prnp 0/0 mice compared to wild-type mice. Following these descriptions, the consequences of Prnp absence in memory, learning, and behavior lead to variable results in studies using mice carrying FGs [24,[45][46][47][48] or not [42,49].…”
Section: Introductionmentioning
confidence: 99%